Avaliação de diferentes formas de preservação e desenvolvimento in situ de folículos ovarianos pré-antrais caprinos - Ferreira, Marcos Antonio Leal (2010)
This study evaluated the effect of indole-3-acetic acid (IAA) in the activation of goats preantral follicles (FOPA). Were used four pairs of ovaries of adult mixed breed goats. Each ovarian pair was divided into 23 fragments. One fragment was fixed for histology and other fragment was using to follicular isolation procedure. The remaining fragments were cultured in 1.0 ml of Minimum Essential Medium (MEM) or MEM supplemented with IAA at concentrations of 10, 40, 100, 500 or 1000 ng/mL. The in vitro culture was performed at 39°C in incubator with 5% CO2 for 1, 3 and 5 days. After in vitro culture was evaluated histological integrity and viability of FOPA. The addition of 100 ng/ml of IAA to MEM showed a significant increase in follicles transition in the third day of in vitro culture, characterizing follicular activation. Moreover, this concentration was obtained maintaining the histological integrity of PAF by the fifth day of in vitro culture. The viability test confirmed the results of histology. Thus, we conclude that IAA can promote the activation of goats FOPA